DEVELOPMENT OF PROBLEM BASED LEARNING TEACHING MODULES ON GREEN CHEMISTRY MATERIALS - Khoirunnisa, Rahmah; Wijayanti, Imas Eva; Assaat, Lusiani Dewi (UIN Mataram, 2024)
The change from the 2013 curriculum to an Merdeka curriculum requires adjustments for teachers and students. The lack of availability of teaching tools that are in accordance with the Merdeka curriculum and a learning approach that is still teacher-centered makes students less motivated to participate in learning. The purpose of this study is to develop a PBL-based teaching module on green chemistry material by determining the validity, practicality, and effectiveness of student responses to the content measured in the teaching module. This research is R&D (Research and Development) research with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) model. The data collection technique used a material and media validation questionnaire involving seven material and media expert validators and was analyzed using the Aiken's V test. Furthermore, the validated teaching module was tested limited to 26 class X phase E students. The development of this PBL-based teaching module obtained results in the validity of the material and media of 0.91 and 0.92 in the